Risk of Developing Severe Alimentary-Constitutional Obesity and Metabolic Disorders: Interventional Comparative Study - M. B. Lyasnikova; N. A. Belyakova; I. G. Tsvetkova; A. A. Rodionov; A. V. Lareva (Кубанский научный медицинский вестник, 2023)
Background. The relevance of alimentary-constitutional obesity, especially its severe forms, is associated with a number of metabolic disorders, subsequently leading to serious chronic noncommunicable diseases.Objective. To identify factors that increase the risk of severe alimentary-constitutional obesity and metabolic disorders.Methods. A follow-up group of 426 patients aged 18 to 65 years was formed among those seeking help from an endocrinologist for overweight or obesity. The diagnosis of alimentary-constitutional obesity was confirmed at the initial examination in the outpatient clinic setting. Depending on the severity of obesity and the type of fat deposition according to anthropometric data (body mass index, waist circumference), the study participants were ratified into two study groups. The research was conducted between 2010 and 2017 in outpatient settings and was based on a cross-sectional comparative study. In order to assess the risk of severe obesity and factors associated with it, the authors studied medical history data, results of physical examination, including blood pressure level, laboratory examination with analysis of carbohydrate, fat metabolism and liver function, assessed eating behaviour, and performed diagnosis of anxiety-depressive disorder. Statistical analysis of the results was carried out using Statistica 10 (StatSoft, USA).Results. Women are more likely to see an endocrinologist with less severe obesity than men. Severe obesity risk is higher in middle-aged and elderly people, as well as in hereditary tainted patients and those having a history of obesity for more than 10 years. Severe obesity itself is a significant risk for metabolic events, with a 4-fold higher risk of hyperglycaemia and hypercholesterolaemia (due to very low density lipoproteins) and a 5-fold higher risk of hyperinsulinaemia and insulin resistance.Conclusion. Analysis of severe obesity risks has shown that earlier personal commitment to a healthy lifestyle is essential for weight loss and subsequent improvement of metabolic parameters, particularly in men and those aged 45 years or older.